Ubuciko Bomlomo: wedding songs as an effective means of communication and education among the Zulu People - Dlamini-Myeni, Bongephiwe; Mbokazi, Samkelisiwe Diligence (Penerbit Universiti Kebangsaan Malaysia, 2024)
Songs are an integral aspect of Zulu folklore, as they are performed in almost all ceremonies in Zulu culture. Every ceremony, or occasion in which people come together, such as a wedding ceremony, (coming of (age), mhlonyana (girls ceremony when they reach womanhood) or a funeral gathering, has particular songs associated with it. The aim of this paper was to explore the effectiveness of wedding songs as a means of communication and education in Zulu culture. The researchers first discussed the importance of music in African societies and secondly examined its role as a means of communication and education. The study adopted a qualitative approach located within the interpretivist paradigm. Ten songs were selected to illustrate how artists use songs to convey social messages. The songs were analysed using the critical discourse analysis approach. The researchers argued that the Zulu people compose songs to record a certain event or convey a social message. Thus, wedding songs do not only entertain people at a particular gathering or ceremony but communicate crucial messages that are educational at the same time. This article has revealed that most of the Zulu wedding songs contain repetitions that emphasise a certain word with an important social message. Therefore, the style and linguistic features of a song play a crucial role in emphasising the message embedded in it.